Porous carbon-coated titania prepared by in-situ polymerization of styrene and its catalytic and photocatal activities in oxidation of alkenes [electronic resource] - Surya Lubis, 1969-; Hadi Nur, supervisor; Lee, Siew Ling, supervisor; Leny Yuliati, supervisor; Fakulti Sains (2013)
Thesis (Ph.D (Chemistry)) - Universiti Teknologi Malaysia, 2013